The relationship between subject matter knowledge and teaching effectiveness of undergraduate chemistry peer facilitators - Boothe, J. R; Barnard, R. A; Peterson, L. J; Coppola, B. P (Chemistry Education Research and Practice, 2018)
Use of peer instruction and facilitation has surged in undergraduate education at large colleges and universities in recent years. Studies on peer instruction have been directed primarily at student learning gains and affective outcomes among the facilitators. For peer instructors, the relationship between their teaching effectiveness and their foundational content knowledge is assumed but understudied. In an effort to promote instructional coherence ( i.e. , instructional same-pageness) in the introductory organic chemistry program at the University of Michigan, we observed peer-led study group facilitators' involvement in their study groups (as teachers of groups of 6-12 students) and in a companion course (as learners) designed to reinforce and enhance their content knowledge. Audiovisual recordings of the facilitators in both the companion course and, for ten of them, leading their study groups, were captured over each of the two week periods covering the topics of stereochemistry and also conformational analysis. Recordings were subsequently coded for topic and correctness in presentation of subject matter. Errors made in either study group or the companion course were investigated for error resolution (corrected or uncorrected), source of error, and propagation of corrected errors. Analysis of recordings revealed that facilitators who have their own errors corrected in the companion course, or observe their peers' errors corrected in the companion course, correctly describe these concepts in study groups. On examining errors made by facilitators when they are leading study group sessions, a backwards analysis showed consistently that either the topics had not been addressed in the antecedent companion course, or the facilitator was not actively engaged with the discussion when the topics were being discussed. These findings have implications to inform not only our own implementation of peer-led study groups, but also those interested in designing subject matter companion courses for peer leaders in other instructional settings.